Colonic Polyp Regression After Nous-209 Cancer Immunotherapy: A Clinical Trial Case Report - Marina Crespo-Cruz; Manuel Rodriguez-Justo; Adam Humphries; Andrew Plumb; Anthony Antoniou; Kevin Monahan; Sarah Runswick; Alessia Capone; Laura Antonucci; Irene Garzia; Elisa Micarelli; Elisa Scarselli; et al. (Journal of Immunotherapy and Precision Oncology, 2026)
ABSTRACT Immunotherapy is an established treatment for mismatch repair–deficient (dMMR) colorectal cancer (CRC), driven by increased neoantigen formation and enhanced responsiveness to immune checkpoint inhibitors. Nous-209 is a polyvalent viral vector immunotherapy under investigation in combination with pembrolizumab in the NOUS-209-01 clinical trial (ClinicalTrials.gov Identifier: NCT04041310) in patients with dMMR CRC. Here, we report on a participant of the NOUS-209-01 trial who achieved a complete pathologic response and significant regression of colonic polyps following treatment with Nous-209 in combination with pembrolizumab and a right hemicolectomy. Genetic testing ruled out Lynch syndrome and mosaicism of Lynch syndrome–associated genes. The patient remains relapse free and under active surveillance 18 months after treatment initiation. Three months after treatment ended, the patient experienced an episode of grade 3 immune-mediated colitis and this improved after infliximab treatment. The clinical and immunologic findings suggest the potential for Nous-209 immunotherapy, in combination with pembrolizumab, to induce regression of both malignant and premalignant colonic lesions. To our knowledge, this is the first report of an immunotherapy combination to reduce premalignant polyps in a patient who does not have Lynch syndrome.